PENGARUH KONSENTRASI DAN LAMA PERENDAMAN A. pintoi DENGAN URIN TERNAK SAPI TERHADAP PERTUMBUHAN TANAMAN A. pintoi - Lumban Gaol, Novalia; Kaunang, Ch. L.; ., Rustandi; Dompas, F. (Universitas Sam Ratulangi, 2017)
INFLUENCE OF CONCENTRATION AND SOAKING TIME OF A. pintoi IN THE COW URINE ON PLANT GROWTH. Cow urine has an auksin a, auksin b, and IAA (hetero auksin) that can stimulate plant roots. The present study was conducted to determine the influence of concentration and soaking time in the cow urine on Arachis pintoi (A. pinto) growth. This study used Completely Randomized Design (CRD) in Factorial arrangement with 2 factors A and B. Factor A= urine concentration: A1 = urine 75% + water 25% and A2; urine 50% + water 50%; and factor B = soaking time: B1 = 1 hour; B2 = 2 hours; Dan, B3 = 3 hours. Treatments were replicated 4 times. Parameters measured were: leaves amount (sheets), plant length (cm), and root weight (g). Research results showed that mean leaves amount ranged from 41,65 to 46,77 sheets, plant length 35,97-36,67 cm, and root weight 1,95-1,72 g. Utilization of cow urine with a different concentration and soaking time gave a non significant different (P>0.05) on leaves amount, plant length, and root weight. It can be concluded that cow urine concentration and soaking time do not effect leaves amount, plant length, and root weight of Arachis pintoi (A. pinto). Key words:Â Cow urine concentration, Soaking time,Â A. pintoi.